2016
DOI: 10.21009/jimd.v16i1.1185
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Rehabilitasi Dan Pola Pembinaan Terhadap Pecandu Narkotika Di Balai Besar Rehabilitasi Badan Narkotika Nasional Indonesia Lido Bogor

Abstract: ABSTRACT This study aims to obtain empirical data, and reliable information about the effectiveness of rehabilitation and development patterns of the drug addict at the Center for Rehabilitation of the National Narcotics Agency Indonesia-Lido, Bogor. The method used is descriptive qualitative. The pattern of development in the institution more emphasis on behavior change, by conducting medical rehabilitation and social rehabilitation. Rehabilitation is divided into two major phases, namely the phase of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition to counselling, medical drug rehabilitation needs to be integrated into counselling services (Han, 2018) because rehabilitation helps drug addicts from addiction (Han, 2018) because rehabilitation helps drug addicts from addiction (Lysa Angrayni & Yusliati, 2018). Comprehensively, the narcotics rehabilitation program is a series of coordinated and integrated efforts consisting of medical struggles, mental guidance, psychosocial, religion, education and vocational training to increase adaptability, independence and self-help, and achieve functional skills after sharing their potential, both physical, mental, social and economic (Timoera & Martono, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to counselling, medical drug rehabilitation needs to be integrated into counselling services (Han, 2018) because rehabilitation helps drug addicts from addiction (Han, 2018) because rehabilitation helps drug addicts from addiction (Lysa Angrayni & Yusliati, 2018). Comprehensively, the narcotics rehabilitation program is a series of coordinated and integrated efforts consisting of medical struggles, mental guidance, psychosocial, religion, education and vocational training to increase adaptability, independence and self-help, and achieve functional skills after sharing their potential, both physical, mental, social and economic (Timoera & Martono, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of BNN research in collaboration with the Indonesian Center for Research and Health in 2011, that the prevalence of drug abusers in Indonesia has reached 2.23% or about 4.2 million people from the total population (aged 10-59 years). In 2015, the number of drug abusers was ± 2.8% or equivalent to ± 5.1-5.6 million people from the Indonesian population [1]. The results of a national survey conducted by the National Narcotics Agency (BNN), in collaboration with the Center for Research on Pranata, University of Indonesia, showed the prevalence of drug-psychotropic abuse among junior, high school, and tertiary students in 30 provincial capitals in 2013 by 3.4%.…”
Section: Introductionmentioning
confidence: 99%